The ten-station judo ability test: A test of physical and skill components - Lidor, R.; Melnik, Y.; Bilkevitz, A.; Falk, B. (Strength and Conditioning Journal, 2006)
The purpose of this article is to present a judo-specific ability test to be used by coaches who work with young judokas.The test is composed of 10 stations. In 5 of the stations the judoka performs physical ability exercises related to judo, and in the remaining stations the judoka performs judo-specific skills.This article provides the rationale for the test as well as specific instructions for each station.